Social Media exposure and Psychological problems during COVID-19 outbreak: A cross-sectional study - Bharat, (International Journal of Psychosocial Rehabilitation, 2024)
The coronavirus disease (Covid-19) has caused depression, anxiety, confusion, changed students living conditions,including commuting restrictions, fear of disease transmission, drugs addictions and closure of coaching institutions,schools, colleges, universities and businesses, and brought about devastating psychological impacts. However, mostprevious studies only have focused on clinical data. In this study the research scholar assessed the prevalence ofpsychological problems and examines their association with social media exposure. A cross-sectional study amongstudents of Kurukshetra University was conducted during 24th March to 30th March 2020.Online survey was used to do rapid assessment. Total of 50 participants of various department of university wereinvolved in the current study. The prevalence of depression, anxiety was 70.9% during COVID-19 outbroke. Morethan 80% of participants reported frequently exposed to social media. This study found that there was highprevalence of psychological problems, which positively associated with frequently SME during the COVID-19outbreak. These findings implicated that the Indian government need pay more attention to psychological problems,especially depression and anxiety among students.